2017
DOI: 10.48550/arxiv.1712.07211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast Quantum Algorithm for Solving Multivariate Quadratic Equations

Abstract: In August 2015 the cryptographic world was shaken by a sudden and surprising announcement by the US National Security Agency (NSA) concerning plans to transition to post-quantum algorithms. Since this announcement post-quantum cryptography has become a topic of primary interest for several standardization bodies. The transition from the currently deployed public-key algorithms to post-quantum algorithms has been found to be challenging in many aspects. In particular the problem of evaluating the quantum-bit se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another approach which is worth exploring is Zhuang-Zi [16] which provides a new technique to solve system of multivariate polynomial equations over a finite field. In the post quantum paradigm, efficient methods for solving these system of equations are illustrated in [11] (only for boolean case), and [13] (linear system of equations). [12] entails a quantum algorithm for solving non linear system of equations in GF(q = p k ) which might be used for improving the proposed method in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach which is worth exploring is Zhuang-Zi [16] which provides a new technique to solve system of multivariate polynomial equations over a finite field. In the post quantum paradigm, efficient methods for solving these system of equations are illustrated in [11] (only for boolean case), and [13] (linear system of equations). [12] entails a quantum algorithm for solving non linear system of equations in GF(q = p k ) which might be used for improving the proposed method in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We have implemented the intersection method with the help of MAGMA [10]. In the post quantum era, we expect that we can solve the system of equations using the methods as illustrated in [11] [12] [13]. We do not expect that the intersection method would be an alternative to Shor's algorithm for solving EC-DLP [14] in the postquantum paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [22], the authors present a quantum version of BooleanSolve [23], which is currently the fastest asymptotic algorithm for classically solving systems of non-linear Boolean equations, that takes advantage of Grover's quantum algorithm. Note that Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[24] also proposed a new Gröbner-based quantum algorithm for solving quadratic equations with a complexity comparable to QuantumBooleanSolve (we refer to Ref. [22] for further details). Finally, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…So any problem relates to searching can be improved directly by Grover's algorithm in quantum computer. More importantly, Grover's algorithm can achieve speedup (sometimes not just quadratic speedup) to many NP complete problems, such as 3-SAT [2], existence of Hamiltonian cycle [29], quadratic Boolean equations solving [16], etc. Unfortunately, it has been shown that Grover's algorithm is optimal [5,7], so there does not exist more efficient quantum algorithms to solve the searching problem.…”
Section: Introductionmentioning
confidence: 99%